Construção e validação de um modelo de comunicação não-verbal para o atendimento de enfermagem a pacientes cegos - Rebouças, Cristiana Brasil de Almeida (2008)
The goal was to validate a non-verbal communication model for nursing care delivery to blind clients, based on the reference framework by E.T. Hall (1986). This methodological research was developed at the LabCom_Saúde research lab of the Nursing Department at Ceará Federal University between October 2007 and June 2008. Fifteen blind people and 15 nurses were selected for each group, i.e. trained and non-trained, both with the same characteristics. The blind were contacted through the Ceará State Association of the Blind (ACEC) and the nurses through the Academic Centers (CAs). In the non-trained group, data were collected in April 2008 through consultations. These took place inside the LabCom_Saúde and data were collected through movie recordings. The studies carried out about Hall’s theory (1986) represented the first step to construct the model. The nursing consultation was subdivided in four phases, which were called care phases. In each phase, orientations are given for the nurse’s actions and the action is described, as well as how this action should take place. Care phase 1 refers to the organization of the environment to develop the Nursing Consultation (CEnf). In care phase 2, the nurse should receive the patient at the entry of the consultation room to introduce him/her into the environment where the consultation will take place, greet the patient and inform where furniture and objects are located. Care phase 3 addresses the development of the CEnf itself. Care phase 4 constitutes the final phase of the non-verbal communication model and focuses on how to end the consultation and close off communication with the patient. After its construction, the Model was submitted to face and content validation. It was analyzed by three specialists in non-verbal communication specialists, a number already adopted in earlier studies. The suggestions included in the model referred to range, presentation form and content representativeness. Next, the second validation phase started, through which the model was tested. The nurses and blind people were trained in terms of the communication techniques that are important in the use of non-verbal communication as well as the use of the Model with blind people. Data were collected with the help of three film cameras that recorded the entire nursing consultation among the nurse, the blind and the companion, if present. To analyze the movie data, three other judges were chosen, who were nurses and students from the Graduate Nursing Program at Ceará Federal University, master’s and doctoral level. They were trained on how to use to nurse-blind non-verbal communication analysis instrument (CONVENCE) and the model validation instrument. As this was a double-blind study, the judges were not informed about which group – control or experimental - they were analyzing. The collected data were inserted in an electronic worksheet, using SPSS software, version 14.0, and analyzed as absolute frequencies through univariate table. To analyze the association between the variables and the nurses in the control and experimental groups, the chi-square (χ2) test and the maximum likelihood estimation were used. Guidelines for research involving human beings were complied with, in accordance with Resolution 196/96 by the Brazilian Ministry of Health. The comparison between care phase 1 actions in the trained and non-trained group showed that the trained group obtained excellent results (p<0.0001) on four of the five items under analysis. The only exception was the “temperature” item, with an approximately equal proportion on the scale. Table 3 shows that, when comparing care phase 2 actions between the groups, the trained group obtained an excellent result (p<0.05) on all items under evaluation. Hence, statistically significant associations were found for all actions. As to the results obtained in Table 4, excellent results are observed (p<0.05) on eight of the nine items assessed for the trained group in comparison with the non-trained group in care phase 3. Only the item related to “following the CEnf script” remained close to the test value, highlighting that this action obtained a strong association score. Data in Table 5 also showed excellent results (p<0.05) for the trained group in comparison with the non-trained group for three of the four actions developed in care phase 4. As observed in Table 6, all items contributed to the internal reliability of the Nurse-Blind Non-Verbal Communication Model. Through this research, it is concluded that nurses and even nursing students need to implement this Non-Verbal Communication Model with a view to effective and affective care, especially for patients who need to understand and be understood in their daily life. The hypothesis is confirmed that the Nurse-Blind Non-Verbal Communication Model is effective in nursing consultations with blind patients.